Identify main components for performance assessment of schools in favorable situation - Taheri, Ahmad; Taghipour zahir, Ali; Jafari, Parivash (Iranian Journal of Educational Sociology, 2022)
Purpose: The aim of this study was to identify the main components of school performance evaluation in desirable condition. Methodology: The present study was a descriptive cross-sectional study. The statistical population of the study consisted of 1980 high school principals who were selected based on Cochran's formula of 322 students using cluster-cluster sampling method. Educational management (including 15 university professors, 20 administrators and 15 school administrators) selected through purposive sampling, semi-structured interviews were conducted, primary components identified and then identified by the researcher to determine the final components. It had 172 items and its face validity and content validation by Tidopa experts for it was 75/0 using Cronbach's alpha, was used. Data were analyzed using exploratory factor analysis and structural equations. Findings: The findings indicated that the following components could be considered for evaluating the performance of 12 components and 172 sub-components: 1- Management and leadership 2- Administrative and financial affairs 3- Teaching processes- Learning and planning 4-Axis programs 5-Information technology and intelligence 6-Physical space and equipment 7-Empower teachers and staff 8-Supplemental, extracurricular activities 9-Organizational climate and organizational culture10-Interaction with school environment and Gaining Experiences11- Physical Education, Health and Well-being 12- Staff Involvement, Parents and Students in School Affairs Conclusion: School management has a very important role in school performance. Therefore, school management and leadership as the main pillar of schools should play a scientific role and with respect to good human relations which will play an important role in enhancing school performance. Keywords: Evaluation, Performance, Schools, Desire.